Law Enforcement Problems in Prosecuting Crime in the Capital Market - Qolbi, Muhammad Ainun; Dimyati, Dimyati (Maliyah : Jurnal Hukum Bisnis Islam, 2024)
Abstract: This study focuses on the evolution and challenges of law enforcement within Indonesia's capital market. The capital market plays a pivotal role in the nation's economic development and financial services. The establishment of the Financial Services Authority (OJK) aims to ensure orderly, transparent, and fair financial activities, striving for stability and protecting the interests of consumers. However, despite the market's modernization, the capital market faces growing challenges related to criminal activities. These challenges stem from outdated laws, inadequate law enforcement, and the dynamic nature of market crimes. Such offenses include fraud, market manipulation, insider trading, and unregulated activities like short selling. The paper addresses the need to identify and address the escalating violations and crimes within the capital market, emphasizing the complexities of providing evidence for these modern, technology-driven transactions. Ultimately, the effectiveness of sanctions relies on robust law enforcement to maintain a secure and trustworthy capital market. This analysis discusses the unique characteristics of criminal activities within the capital market, focusing on information as the primary object of these offenses. Perpetrators rely on their market insights rather than physical actions, making detection and proof challenging. Crimes in the capital market entail administrative, criminal, and civil penalties, primarily centered on fraud, market manipulation, and insider trading. The legal framework in Law No. 8 of 1995 on Capital Markets outlines these offenses and their corresponding penalties. Law enforcement mechanisms transition from administrative to civil and finally to criminal sanctions. Ensuring ethical standards within the business realm is crucial, requiring codified regulations to maintain market integrity and protect investors. Keywords: Law Enforcement; Capital Market Crime; Financial Services Authority. Abstrak: Penelitian ini berfokus pada evolusi dan tantangan penegakan hukum di dalam pasar modal Indonesia. Pasar modal memiliki peran penting dalam pengembangan ekonomi dan layanan keuangan nasional. Pembentukan Otoritas Jasa Keuangan (OJK) bertujuan untuk memastikan kegiatan keuangan yang tertib, transparan, dan adil, dengan berupaya menjaga stabilitas serta melindungi kepentingan konsumen. Namun, meskipun pasar telah mengalami modernisasi, pasar modal menghadapi tantangan yang semakin besar terkait aktivitas kriminal. Tantangan ini berasal dari undang-undang yang sudah usang, penegakan hukum yang kurang memadai, serta sifat dinamis dari kejahatan pasar. Pelanggaran tersebut meliputi penipuan, manipulasi pasar, perdagangan orang dalam, dan aktivitas yang tidak diatur seperti penjualan kosong (short selling). Makalah ini membahas perlunya mengidentifikasi dan mengatasi peningkatan pelanggaran serta kejahatan di dalam pasar modal, dengan menekankan kompleksitas pembuktian dalam transaksi modern yang didorong oleh teknologi. Pada akhirnya, efektivitas sanksi bergantung pada penegakan hukum yang kuat untuk menjaga pasar modal yang aman dan terpercaya. Analisis ini membahas karakteristik unik dari aktivitas kriminal dalam pasar modal, dengan fokus pada informasi sebagai objek utama dari kejahatan tersebut. Pelaku mengandalkan wawasan mereka terhadap pasar daripada tindakan fisik, sehingga deteksi dan pembuktian menjadi sulit. Kejahatan di pasar modal mencakup sanksi administratif, pidana, dan perdata, yang terutama berfokus pada penipuan, manipulasi pasar, dan perdagangan orang dalam. Kerangka hukum dalam Undang-Undang No. 8 Tahun 1995 tentang Pasar Modal mengatur pelanggaran-pelanggaran ini beserta sanksinya. Mekanisme penegakan hukum bertransisi dari sanksi administratif ke perdata dan akhirnya ke pidana. Menjaga standar etika dalam dunia bisnis sangat penting, yang membutuhkan regulasi yang dikodifikasi untuk menjaga integritas pasar dan melindungi investor. Kata Kunci: Penegakan Hukum; Tindak Pidana Pasar Modal; Otoritas Jasa Keuangan.